(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of seasonal influenza vaccination, identify associated factors, and assess post-vaccination reactions among children aged 6 months to under 5 years at Phu Tho Obstetrics and Pediatrics Hospital in 2022. Methods: A cross-sectional descriptive study was conducted on 3,801 children aged 6 months to under 5 years attending the vaccination center from September 2021 to August 2022. Data were collected from immunization records and supplemented by interviews when necessary. Descriptive statistics and Chi-square tests were used for analysis, with p < 0.05 considered statistically significant. Results: The proportion of children receiving at least one dose of influenza vaccine was 67.5%. Among vaccinated children, those aged under 3 years accounted for 86.4%, and 73.0% resided in urban areas. The proportion of incomplete primary vaccination remained high (64.9%), while the booster vaccination rate was very low (0.4%). Maternal education level and household economic status were significantly associated with vaccine uptake (p < 0.05). Post-vaccination reactions were mostly mild, with the most common being local pain/swelling (17.5%) and vomiting (12.9%), typically occurring within the first day. Fever was uncommon (1.2%) and generally mild. Conclusion: Influenza vaccine uptake was relatively high; however, completion of the primary series and booster doses remained suboptimal. Socioeconomic factors and vaccine availability played important roles. The vaccine demonstrated a favorable safety profile with mostly mild, self-limited reactions.